2018
DOI: 10.1080/10790268.2018.1456768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pelvis postural systems in spinal cord injury patients: Outcome research

Abstract: This study has allowed two significant conclusions: the central role of the interplay between the patient and occupational therapist in the decision role and the clear evidence that patients with spinal cord injury felt definite differences between cushion stability and were able to indicate a specific typology providing the best satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…A research group of Sapienza University of Rome and Rehabilitation & Outcome Measures Assessment (ROMA) association conducted the study. The research group dealt with the validation of different outcome measures in Italy 20,21,22,23 . The institutional review board of Sapienza Università di Roma approved the study and guaranteed ethical standards and procedures.…”
Section: Methodsmentioning
confidence: 99%
“…A research group of Sapienza University of Rome and Rehabilitation & Outcome Measures Assessment (ROMA) association conducted the study. The research group dealt with the validation of different outcome measures in Italy 20,21,22,23 . The institutional review board of Sapienza Università di Roma approved the study and guaranteed ethical standards and procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The institutes composed the Institutional Review Board and have guaranteed ethical standard and procedures. In the last years, the research group has dealt different validation studies in Italy (48)(49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the NAHS is considered a good instrument for the evaluation of young and active patients with hip disease. NAHS is a good instrument in clinical practice and in research studies because it is very simple, self-administered and quick to complete (only 5 minutes) and to understand for a maximum compliance of the patient and it is specific for young and physically active individuals [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%